'They built a whole lot like that in the fifties and sixties': Ishiguro and the ghosts of English institutions'. Issue 10 (3rd October 2022) - Dean, Dominic
ABSTRACT: For Kazuo Ishiguro's characters, institutions endure as ghosts long after their original functions have ceased. Though such institutions appear in Ishiguro's work from Japan to Shanghai to central Europe, this essay argues that Ishiguro's English institutions register his subtle yet deeply-rooted critique of the British state's particular modern crises, exposing its attempts to replace political plurality and historical contingency with an essentialist ideal. Ishiguro's institutions are themselves repeatedly complicit in such attempts, whether oriented towards racial nationalism in The Remains of the Day or the 'Originality' that governs Never Let Me Go - ideologies that ultimately destroy these institutions. The circumstances of that destruction nevertheless expose, ironically and elegiacally, the institution's lost potential. This essay argues that despite their compromised status, these institutions have a real ethical value and even subtle radicalism in haunting Ishiguro's Britain from the pre-state landscape of The Buried Giant to the late modernity of Never Let Me Go . Beginning by identifying this ethical and political potential, proceeding to describe how it registers through the institutional access enjoyed by Ishiguro's protagonists, and finally exploring Ishiguro's provocative response to Britain's recent history, this essay offers a revised interpretation of Ishiguro's English institutions and of their collective significance.